ROS-Scavenging Nanomaterials to Treat Periodontitis - Sui, Lihua; Wang, Jianling; Xiao, Zuoxiu; Yang, Yuqi; Yang, Zhichun; Ai, Kelong (Frontiers in Chemistry, 2020)
The incidence of periodontitis is very high, and up to 45-50% of people are suffering from periodontitis. Periodontitis is caused by pathogens that invade teeth-supporting tissues such as gingiva, periodontal ligament, and alveolar bone. Pathogens trigger host immune responses characterized by the overproduction of reactive oxygen species (ROS). The development of effective ROS scavengers through nanotechnology has been emerging as a promising strategy for the treatment of periodontitis. Nanomaterial-based antioxidants can effectively scavenge ROS, prevent ROS-mediated tissue damage, and relieve inflammation in periodontitis. This mini-review focuses on the generation of ROS in periodontitis and its molecular mechanism of destroying periodontal tissue. Meanwhile, we summarize the research progress of ROS-scavenging nanomaterials in the treatment of periodontitis and discuss the challenges and prospects of its application.